Designing a behaviour change intervention to address the behavioural risk factors for stillbirth: A study protocol [version 1; peer review: 2 approved, 1 approved with reservations] - Richard A. Greene; Keelin O'Donoghue; Tamara Escañuela Sánchez; Molly Byrne; Karen Matvienko-Sikar (HRB Open Research)
Introduction Stillbirth is a devastating outcome that, in some cases, has the potential to be prevented by addressing some of its modifiable risk factors such as smoking, alcohol consumption, illicit drug use, high maternal weight, lack of attendance to antenatal care, and sleep position. The aim of this study will be to design a behaviour change intervention focusing on the behavioural risk factors for stillbirth and based on the COM-B model and the Behaviour Change Wheel (BCW) systematic framework. Methods The first stage of the BCW framework involves understanding the target behaviour and defining the problem in behavioural terms. The second stage involves identifying intervention options, including intervention functions and policy categories. Finally, the third stage involves identifying content and implementation options, including behaviour change techniques (BCTs) and the mode of delivery. We will use multiple studies already conducted in our research team to inform the different stages of the BCW framework, these include a series of systematic reviews of the literature, qualitative interviews with pregnant women, and a survey study with healthcare professionals. Further, we will utilise a stakeholder group to obtain input through the process of the design of the intervention. Discussion This protocol provides a systematic and evidence-based approach to intervention design. The systematic review of the literature, qualitative interviews, and expert consensus workshops will ensure that the intervention design is based on the needs and preferences of pregnant women, healthcare professionals, and stakeholders involved in stillbirth prevention. The proposed intervention could be adapted and implemented in other settings to prevent stillbirth in high-risk populations.